A Case of Cardiac Calcified Amorphous Tumor Presenting with Concomitant ST-Elevation Myocardial Infarction and Occipital Stroke and a Brief Review of the Literature. (24th December 2017) - Kyaw, Kyaw; Latt, Htun; Aung, Sammy San Myint; Roongsritong, Chanwit
Abstract : Cardiac calcified amorphous tumor (CAT) is an extremely rare benign intracavitary tumor of the heart. It may mimic other cardiac tumors and can present with signs or symptoms of systemic embolization. There are limited data regarding CAT in the literature. We report a case of a 68-year-old woman with a cardiac CAT and mitral annular calcification (MAC), who presented with acute ST-elevation myocardial infarction (STEMI) and occipital stroke. After extensive review of the literature, we believe that this case is possibly the first description of a cardiac CAT presenting with STEMI. The CAT was surgically removed, and the diagnosis was confirmed by histology. The patient tolerated the surgery and reported no events at 6-month follow-up.